(untitled) (Kinesiology, 2019)
Abstract: The objective of this study is to examine the three-dimensional foot shape data and determine foot type’s distribution among Chinese children and adolescents. A total of sixteen three-dimensional foot shape variables of 5069 Chinese children were measured through filming, including 3 girth-related variables, 3 length-related variables, 2 width-related variables, and 8 height-related variables. Cluster analysis was performed to classify these three-dimensional feet data of Chinese children and adolescents into three identified foot types, namely Robust Feet, Slender Feet, and Flat Feet, which differ in terms of length, volume, and arch height. Three foot types’ distribution varies across the different foot length groups. The foot types classification may be used in the design of shoe lasts and in the manufacture of comfortable footwear to minimize error fitting. Keywords: foot shape; cluster analysis; shoes making